The Synthesis Of Nanosized Hydroxyapatite Powders - Tan, Su Anne (2007)
Nanometer sized hydroxyapatite particles are synthesized via wet chemical precipitation and characterized. This research studies how key parameters such as the pH of synthesis, and also the reaction, aging and calcination temperatures affect the size and phase purity of the hydroxyapatite produced. The main aim is to determine the optimum condition for producing phase-pure, nano-sized hydroxyapatite with minimum agglomeration, to be used as bone replacement material. A 0.2 M solution of Ca(N03)2.4H20 (Calcium Nitrate Tetrahydrate) and a 0.12 M solution of (NH4)2HP04 (Diammonium Hydrogen Phosphate) are coprecipitated in the presence of a dispersant.